2009
DOI: 10.1007/s00464-009-0598-9
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transhepatic insertion of self-expanding short metal stents for biliary obstruction before resection of pancreatic or duodenal malignancy proves to be safe and effective

Abstract: Percutaneous insertion of short metal stents provides a safe and effective alternative to endoscopic stent placement for treating jaundice preoperatively in patients with potentially resectable tumors around the pancreatic head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…A meta-analysis comparing percutaneous versus endoscopic biliary drainage demonstrated no significant difference with regards to mortality, complications, or therapeutic response rates, making percutaneous biliary drainage a validated second-line therapy in these patients [109]. Alternatively, in patients who would otherwise be a candidate for endoscopic internal metallic stent placement, percutaneous placement of self-expanding stents has demonstrated safety and effectiveness similar to their endoscopically placed counterparts [110][111][112].…”
Section: Stent Optionsmentioning
confidence: 99%
“…A meta-analysis comparing percutaneous versus endoscopic biliary drainage demonstrated no significant difference with regards to mortality, complications, or therapeutic response rates, making percutaneous biliary drainage a validated second-line therapy in these patients [109]. Alternatively, in patients who would otherwise be a candidate for endoscopic internal metallic stent placement, percutaneous placement of self-expanding stents has demonstrated safety and effectiveness similar to their endoscopically placed counterparts [110][111][112].…”
Section: Stent Optionsmentioning
confidence: 99%
“…Manuscript to be reviewed 1 Table 5. The cluster analysis of 8 clusters Cluster Number of MeSH terms a Cluster analysis 23,34,56,58,69,72,79,82 Stents placement in pancreatic neoplasms 5,9,10,19,21,24,27,36,39,40,41 The complications of stents placement in bile duct neoplasms and pancreatic neoplasms 8,35,45,49,50,52,54,71,73,74,75,76 postoperative complications after stent placement such as pancreaticoduodenectomy 1,2,3,6,11,15,17,18,46,47,51,60,67,80 Stents for the prevention of pancreatic fistula following pancreaticoduodenectomy 12,13,14,22,28,37,48,61,65 Prophylactic pancreatic duct stent can reduce the incidence of post-ERCP pancreatitis (PEP) 4,…”
Section: Figurementioning
confidence: 99%
“…As an example, the covered metal stents reduce the incidence of complications of biliary obstruction caused by pancreatic cancer. It has been reported that percutaneous insertion of short metal stents supplies for a secure treatment, which is beneficial for patients in resectable pancreatic head cancer with jaundice [1]. With in-depth research, an irradiation pancreatic stent may provide longer patency and better patient survival [2].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the covered metal stents reduce the incidence of complications of biliary obstruction caused by pancreatic cancer. It has been reported that percutaneous insertion of short metal stents supplies for a secure treatment, which is beneficial for patients in resectable pancreatic head cancer with jaundice (Briggs et al, 2010). With in-depth research, an irradiation pancreatic stent may provide longer patency and better patient survival (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%